Pembuatan Styrofoam Ramah Lingkungan Dari Pati Singkong (Amilum manihot) Dengan Penambahan serbuk Cangkang Telur (Ova) Sebagai Filler - Ubaidillah Nawwaf Al Fanni ubed; fikri firdausi; Agus Widayoko; Yesi Yuliani (SMA Trensains Muhammadiyah Sragen, 2024)
Styrofoam is a raw material for food packaging that is often used in everyday life. However, styrofoam contains benzene which can cause cancer. It was found that up to 0.59 million tonnes of rubbish entered the sea throughout 2018. One of the most common rubbishes found was Styrofoam rubbish. Styrofoam cannot decompose completely but turns into microplastics which can pollute the environment. So, food packaging is needed that can be degraded by microbes and is safe for the body, namely by making biodegradable foam from cassava stems and egg shells. So far, cassava starch has only been used as a raw material for making food. Likewise, eggshells are just thrown away. Cassava starch contains high carbohydrates, mixed with egg shells which contain CaCO3 and is suitable for making biofoam. This research uses descriptive qualitative, with a focus on making biodegradable foam that is safe for health and environmentally friendly as an effort to utilize cassava starch and eggshell waste. The collection method is through observation. After testing, the water absorption test results were found to be 12.01%, tensile strength 3.12 N/mm2, and biodegradation 12.23%. This figure meets SNI 1969:2008. This research produces a biodegradable foam innovation that is safe for the environment and safe for health as an effort to utilize waste from cassava stems and egg shells.